Resin composition, prepreg, resin-coated film, resin-coated metal foil, metal-clad laminate, and wiring board

By optimizing the composition of polyphenylene ether compounds, maleimide compounds, and titanate compounds in the resin composition, the problem of poor dielectric properties in the prior art has been solved, achieving a balance between high relative permittivity and low dielectric loss factor, making it suitable for high-frequency wiring board materials.

CN123057134APending Publication Date: 2026-11-06PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202580024052.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-28
Filing Date
2025-03-18
Publication Date
2026-11-06

AI Technical Summary

Technical Problem

Existing resin compositions struggle to effectively reduce dielectric loss factor while maintaining a high relative permittivity, especially in high-frequency applications.

Method used

A resin composition containing polyphenylene ether compounds, maleimide compounds, and specific titanate compound fillers is used. By adjusting the content and type of titanate compound fillers, the composition of the resin composition is optimized to achieve a balance between high relative permittivity and low dielectric loss factor.

Benefits of technology

A resin composition with a relatively high dielectric constant and low dielectric loss factor has been developed for high-frequency applications, improving the performance of the cured product and making it suitable as an insulating layer material for high-frequency wiring boards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123057134A_ABST
    Figure CN123057134A_ABST
Patent Text Reader

Abstract

The resin composition contains: a polyphenylene ether compound (A) having a carbon-carbon unsaturated double bond; a maleimide compound (B) having two or more N-substituted maleimide groups in one molecule; and an inorganic filler (C) including a titanate compound filler (C-1), wherein the titanate compound filler (C-1) includes one or more fillers selected from the group consisting of strontium titanate, calcium titanate, and titanium oxide, the total content of the one or more fillers selected from the group consisting of strontium titanate, calcium titanate, and titanium oxide is 50% by mass or more with respect to the total amount of the inorganic filler (C), and the content of the inorganic filler (C) is 100 to 400 parts by mass with respect to 100 parts by mass of the polyphenylene ether compound (A) and the maleimide compound (B).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to resin compositions, prepregs, resin-coated films, resin-coated metal foils, metal foil-coated laminates, and wiring boards. Background Technology

[0002] When wiring boards used in electronic devices, such as those used in antenna modules, are required to handle high frequencies, they must be able to withstand these frequencies. To reduce signal transmission losses, the substrate material of the insulating layer used to construct this high-frequency wiring board must have a low dielectric loss factor. Furthermore, to meet the requirements of antenna miniaturization and finer wiring patterns, the substrate material must also have a high relative permittivity.

[0003] For example, Patent Document 1 describes a resin composition having a high relative permittivity and a low dielectric loss factor, suitable for manufacturing an insulating layer for printed wiring boards, and a prepreg obtained using the resin composition. Specifically, the resin composition describes that it comprises BaTi4O9 (A), a filler material (B) different from BaTi4O9 (A), and a thermosetting resin (C), wherein the average particle size of BaTi4O9 (A) is 0.10 to 1.00 μm, and the composition comprises BaTi4O9 (A) and the filler material (B) in a volume ratio (BaTi4O9 (A): filler material (B)) within the range of 15:85 to 80:20.

[0004] Existing technical documents

[0005] Patent documents

[0006] Patent Document 1: International Patent Publication No. 2022 / 172752 Summary of the Invention

[0007] The object of this invention is to provide a resin composition that yields a cured product with a high relative permittivity and a low dielectric loss factor. Furthermore, the object of this invention is to provide a prepreg, a resin-coated film, a resin-coated metal foil, a metal foil-coated laminate, and a wiring board obtained using this resin composition.

[0008] The inventors conducted dedicated research to solve the above problems, and as a result, the present invention was realized.

[0009] The resin composition of the first technical solution of the present invention comprises: a polyphenylene ether compound (A) having carbon-carbon unsaturated double bonds; a maleimide compound (B) having two or more N-substituted maleimide groups in one molecule; and an inorganic filler (C) comprising a titanate compound filler (C-1), wherein,

[0010] The titanate compound filler (C-1) comprises one or more fillers selected from the group consisting of strontium titanate, calcium titanate, and titanium oxide.

[0011] The total content of one or more fillers selected from the group consisting of strontium titanate, calcium titanate and titanium oxide is 50% or more by mass relative to the total amount of the inorganic filler (C), and is 100 parts by mass or more and 400 parts by mass relative to 100 parts by mass of the polyphenylene ether compound (A) and the maleimide compound (B). Attached Figure Description

[0012] Figure 1 This is a schematic cross-sectional view illustrating an example of a prepreg according to an embodiment of the present invention.

[0013] Figure 2 This is a schematic cross-sectional view illustrating an example of a metal foil laminate according to an embodiment of the present invention.

[0014] Figure 3 This is a schematic cross-sectional view illustrating an example of a wiring board according to an embodiment of the present invention.

[0015] Figure 4 This is a schematic cross-sectional view illustrating an example of a resin-coated metal foil according to an embodiment of the present invention.

[0016] Figure 5 This is a schematic cross-sectional view illustrating an example of a resin-coated film according to an embodiment of the present invention. Detailed Implementation

[0017] The resin composition described in Patent Document 1 primarily achieves a high relative permittivity and a low dielectric loss factor by specifying the physical properties of BaTi4O9, an essential filler material, and the volume ratio of BaTi4O9 to other fillers. However, while this resin composition can increase the relative permittivity to some extent, it is difficult to reduce the dielectric loss factor to the desired value. Furthermore, generally, while including inorganic fillers with high relative permittivity in the resin composition can increase the relative permittivity of the cured product, simply including inorganic fillers with high relative permittivity often leads to an increased dielectric loss factor.

[0018] As mentioned above, the resin compositions reported to date as substrate materials for the insulating layer of wiring boards designed for high-frequency applications still have room for improvement from the perspectives of high relative permittivity and low dielectric loss factor.

[0019] The inventors conducted dedicated research and discovered that, in a resin composition containing a specified polyphenylene ether compound (A), a specified maleimide compound (B), and an inorganic filler (C) comprising a titanate compound filler (C-1), by adjusting the total content of one or more fillers selected from the group consisting of strontium titanate, calcium titanate, and titanium oxide in the titanate compound filler (C-1) in a manner that satisfies specific conditions, a cured resin composition with a high relative dielectric constant and a low dielectric loss factor can be obtained.

[0020] That is, according to the present invention, a resin composition capable of producing a cured material with a high relative permittivity and a low dielectric loss factor can be provided. Furthermore, by using this resin composition, high-performance prepregs, resin-coated films, resin-coated metal foils, metal-coated laminates, and wiring boards can be provided.

[0021] Hereinafter, embodiments of the present invention will be described in detail with reference to the accompanying drawings. It should be noted that the scope of the present invention is not limited to the embodiments described herein, and various modifications can be made without prejudice to the spirit of the present invention.

[0022] <Resin Composition>

[0023] The resin composition involved in this embodiment (hereinafter also referred to as the "resin composition") contains: a polyphenylene ether compound (A) having carbon-carbon unsaturated double bonds; a maleimide compound (B) having two or more N-substituted maleimide groups in one molecule; and an inorganic filler (C) comprising a titanate compound filler (C-1).

[0024] The following details the components contained in the resin composition, the physical properties of the resin composition, the uses of the resin composition, and the preparation method of the resin composition.

[0025] [A] Polyphenylene ether compound with carbon-carbon unsaturated double bonds

[0026] The polyphenylene ether compound (A) having carbon-carbon unsaturated double bonds is not particularly limited as long as it is a modified polyphenylene ether compound whose ends are modified by substituents having carbon-carbon unsaturated double bonds (hereinafter referred to as "modified polyphenylene ether compound (A)"). If the resin composition contains the modified polyphenylene ether compound (A), the dielectric loss factor of the cured resin composition can be reduced. In addition, since the modified polyphenylene ether compound (A) exhibits high reactivity with the maleimide compound (B) described later, it is believed that the glass transition temperature of the cured resin composition and the adhesion of the resin composition to the metal foil can be improved.

[0027] The modified polyphenylene ether compound (A) preferably comprises a polyphenylene ether compound having at least one group selected from the groups shown in formula (1) and formula (2) below. In summary, the modified polyphenylene ether compound (A) preferably comprises a polyphenylene ether compound whose end is modified by at least one group selected from the groups shown in formula (1) and formula (2) below, and has at least one group selected from the groups shown in formula (1) and formula (2) below at the molecule end.

[0028]

[0029] In formula (1), p represents an integer from 0 to 10, Ar represents an aryl group, and R1 to R3 each independently represent a hydrogen atom or an alkyl group.

[0030]

[0031] In formula (2), R4 represents a hydrogen atom or an alkyl group.

[0032] If the modified polyphenylene ether compound (A) contains the polyphenylene ether compound as described above, the dielectric loss factor of the cured resin composition can be reduced more reliably.

[0033] In formula (1) above, the arylene group is not specifically limited. Examples of arylene groups include monocyclic aromatic groups such as phenylene, and polycyclic aromatic groups such as naphthalene ring. In addition, the arylene group represented by Ar in formula (1) above also includes derivatives formed by replacing the hydrogen atoms bonded to the aromatic ring with functional groups such as alkenyl, alkynyl, formyl, alkyl carbonyl, alkenyl carbonyl, and alkynyl carbonyl.

[0034] In formulas (1) and (2) above, the alkyl group is not particularly limited. For example, it is preferably an alkyl group having 1 to 18 carbon atoms, and more preferably an alkyl group having 1 to 10 carbon atoms. Specifically, examples of alkyl groups include methyl, ethyl, propyl, hexyl, and decyl.

[0035] Examples of groups represented by formula (1) above include vinylbenzyl (ethylene benzyl) as shown in formula (3) below. Additionally, examples of groups represented by formula (2) above include acryloyl and methacryloyl.

[0036]

[0037] As the substituent (at least one of the groups shown in formula (1) and formula (2) above), more specifically, examples include: ortho-vinylbenzyl, meta-vinylbenzyl, p-vinylbenzyl, etc., vinylbenzyl (vinylbenzyl); vinylphenyl; acryloyl; methacryloyl, etc. The modified polyphenylene ether compound (A) may have one or more of these substituents.

[0038] The modified polyphenylene ether compound (A) has a polyphenylene ether chain in the molecule, preferably having a repeating unit as shown in the following formula (4) in the molecule.

[0039]

[0040] In formula (4) above, t represents 1 to 50. Furthermore, R5 to R8 each independently represent any one of the groups selected from the group consisting of hydrogen atom, alkyl, alkenyl, alkynyl, formyl, alkylcarbonyl, alkenylcarbonyl, and alkynylcarbonyl. Among these, R5 to R8 are preferably each independently a hydrogen atom and an alkyl group.

[0041] The alkyl group in R5 to R8 is not particularly limited, but is preferably an alkyl group having 1 to 18 carbon atoms, and more preferably an alkyl group having 1 to 10 carbon atoms. Specifically, examples of alkyl groups include methyl, ethyl, propyl, hexyl, decyl, etc.

[0042] The alkenyl group is not particularly limited, but is preferably an alkenyl group with 2 to 18 carbon atoms, and more preferably an alkenyl group with 2 to 10 carbon atoms. Specifically, examples of alkenyl groups include vinyl, allyl, and 3-butenyl.

[0043] The alkynyl group is not particularly limited, but is preferably an alkynyl group with 2 to 18 carbon atoms, and more preferably an alkynyl group with 2 to 10 carbon atoms. Specifically, examples of alkynyl groups include ethynyl and prop-2-yn-1-yl (propynyl).

[0044] The alkyl carbonyl group is not particularly limited as long as it is a carbonyl group substituted with an alkyl group. For example, an alkyl carbonyl group with 2 to 18 carbon atoms is preferred, and an alkyl carbonyl group with 2 to 10 carbon atoms is more preferred. Specifically, examples of alkyl carbonyl groups include acetyl, propionyl, butyryl, isobutyryl, neopentyl, hexanoyl, octanoyl, cyclohexyl carbonyl, etc.

[0045] The alkenyl carbonyl group is not particularly limited as long as it is a carbonyl group that has been substituted with an alkenyl group. For example, an alkenyl carbonyl group with 3 to 18 carbon atoms is preferred, and an alkenyl carbonyl group with 3 to 10 carbon atoms is more preferred. Specifically, examples of alkenyl carbonyl groups include acryloyl, methacryl, crotonyl, etc.

[0046] The alkynyl carbonyl group is not particularly limited as long as it is a carbonyl group substituted with an alkynyl group. For example, an alkynyl carbonyl group with 3 to 18 carbon atoms is preferred, and an alkynyl carbonyl group with 3 to 10 carbon atoms is more preferred. Specifically, examples of alkynyl carbonyl groups include propynyl groups.

[0047] Examples of modified polyphenylene ether compounds (A) include, for example, the polyphenylene ether compound shown in formula (5) below, the polyphenylene ether compound shown in formula (6) below, etc. Furthermore, the modified polyphenylene ether compound (A) can be used alone, or two or more modified polyphenylene ether compounds (A) can be used in combination.

[0048]

[0049]

[0050] In equations (5) and (6) above, R9~R 16 and R 17 ~R 24 Each of these groups independently represents any one of the following groups: hydrogen atom, alkyl, alkenyl, alkynyl, formyl, alkylcarbonyl, alkenylcarbonyl, and alkynylcarbonyl. Among these, R9 to R9... 16 and R 17 ~R 24 Preferably, each is a substituent selected from the group consisting of hydrogen atoms and alkyl groups. X1 and X2 each independently represent substituents having carbon-carbon unsaturated double bonds. A and B represent repeating units as shown in formula (7) and formula (8) below, respectively. In addition, in formula (6) above, Y represents a straight-chain, branched, or cyclic hydrocarbon with 20 or fewer carbon atoms.

[0051]

[0052]

[0053] In equations (7) and (8) above, m and n preferably represent 0 to 20, respectively. The sum of m and n is preferably represented as a value from 1 to 30. R 25 ~R 28 and R 29 ~R 32 Each can independently represent any group selected from the group consisting of hydrogen atom, alkyl, alkenyl, alkynyl, formyl, alkylcarbonyl, alkenylcarbonyl, and alkynylcarbonyl. Among these, R... 25 ~R 28 and R 29 ~R 32 Preferably, each is an independent hydrogen atom or an alkyl group.

[0054] In summary, R9 to R in equations (5) to (8) above are... 32 The specific examples listed are the same as R5 to R8 in the above formula (4).

[0055] The modified polyphenylene ether compound (A) shown in formula (5) and the modified polyphenylene ether compound (A) shown in formula (6) are not particularly limited as long as they are compounds that satisfy the above structure.

[0056] Furthermore, in the above formula (6), Y can be represented by groups such as those shown in the following formula (9).

[0057]

[0058] In the above formula (9), R 33 and R 34 Each can be independently represented by any group selected from the group consisting of hydrogen atoms and alkyl groups. Examples of alkyl groups include methyl. Examples of groups represented by formula (9) above include methylene, methylmethylene, dimethylmethylene, etc. Among these, the group represented by formula (9) above is preferably dimethylmethylene.

[0059] As a specific example of the modified polyphenylene ether compound (A) shown in formula (5) above, a polyphenylene ether compound shown in formula (10) below can be cited as an example.

[0060]

[0061] As specific examples of the modified polyphenylene ether compound (A) shown in formula (6) above, examples of polyphenylene ether compounds shown in formula (11) below and polyphenylene ether compounds shown in formula (12) below can be listed.

[0062]

[0063]

[0064] In equations (10) to (12) above, m and n are the same as m and n in equations (7) and (8) above. In equations (10) and (11) above, R1 to R3, p and Ar are the same as R1 to R3, p and Ar in equation (1) above. In equations (11) and (12) above, Y is the same as Y in equation (6) above. In equation (12) above, R4 is the same as R4 in equation (2) above.

[0065] The modified polyphenylene ether compound (A) can be synthesized by any method known to those skilled in the art. As an example of a synthesis method, one can cite the following: dissolving the polyphenylene ether compound and a compound having substituents with carbon-carbon unsaturated double bonds and halogen atoms in a solvent, and stirring the mixture, preferably in the presence of an alkali metal hydroxide and a phase transfer catalyst.

[0066] Alternatively, commercially available modified polyphenylene ether compound (A) can also be used. Examples of commercially available products include "OPE-2st 1200" and "OPE-2st 2200" manufactured by Mitsubishi Gas Chemical Co., Ltd., and "SA9000" manufactured by SABIC Innovative Plastics Co., Ltd.

[0067] The modified polyphenylene ether compound (A) is not particularly limited, but preferably includes a modified polyphenylene ether compound having at least one of a weight-average molecular weight (Mw) and a number-average molecular weight (Mn) of 1000 to 5000.

[0068] Specifically, the weight-average molecular weight (Mw) of the modified polyphenylene ether compound (A) is preferably 1000 to 5000, more preferably 1000 to 4000. In this specification, the weight-average molecular weight (Mw) of the modified polyphenylene ether compound (A) refers to the value measured using a conventional molecular weight determination method, namely gel permeation chromatography (GPC). Furthermore, when the modified polyphenylene ether compound (A) has repeating units as shown in formula (4) above (e.g., repeating unit t as shown in formula (4) above), t is preferably a value that brings the weight-average molecular weight of the modified polyphenylene ether compound (A) within the above range. It is believed that if the weight-average molecular weight (Mw) of the modified polyphenylene ether compound (A) is within the above range, the low dielectric loss factor of the cured product, the glass transition temperature, and the adhesion of the resin composition to the metal foil are more superior.

[0069] The number average molecular weight (Mn) of the modified polyphenylene ether compound (A) is not particularly limited, but is preferably 1,000 to 5,000, and more preferably 1,000 to 4,000.

[0070] The average number of substituents at the molecule end of each molecule of the modified polyphenylene ether compound (A) (the number of terminal functional groups of the modified polyphenylene ether compound (A)) is not particularly limited. Specifically, the number of terminal functional groups is preferably 1 to 5, more preferably 1 to 3. It is considered that if the number of terminal functional groups is within the above range, it is more suitable from the viewpoint of the heat resistance of the cured product and the shelf life, flowability and formability of the resin composition.

[0071] "Number of terminal functional groups of modified polyphenylene ether compound (A)" refers to the numerical value representing the average value of that substituent in each molecule of all modified polyphenylene ether compounds (A) present in 1 mole of modified polyphenylene ether compound (A).

[0072] The content of the modified polyphenylene ether compound (A) is not particularly limited, but is preferably 30% by mass or more, more preferably 35% by mass or more, and even more preferably 40% by mass or more, relative to the total amount of resin component containing the modified polyphenylene ether compound (A). Furthermore, the content of the modified polyphenylene ether compound (A) relative to the total amount of resin component containing the modified polyphenylene ether compound (A) is preferably 90% by mass or less, more preferably 75% by mass or less, and even more preferably 65% ​​by mass or less.

[0073] It should be noted that, in this specification, "resin component" refers to the modified polyphenylene ether compound (A) and the maleimide compound (B) described later, as well as any curing agent described later included in the resin composition.

[0074] Furthermore, the mass ratio of the modified polyphenylene ether compound (A) to the maleimide compound (B) described later (modified polyphenylene ether compound (A): maleimide compound (B)) is preferably 20:80 to 80:20, more preferably 30:70 to 70:30, and even more preferably 40:60 to 60:40. By keeping the mass ratio of the modified polyphenylene ether compound (A) to the maleimide compound (B) within the above range, the relative dielectric constant of the cured product can be maintained to a higher degree, and the dielectric loss factor can be reduced to a lower value. Moreover, from the viewpoint of high adhesion, low coefficient of thermal expansion, and high glass transition temperature, these effects can be obtained more reliably.

[0075] [Maleimide compounds (B) having two or more N-substituted maleimide groups in one molecule]

[0076] Maleimide compound (B) having two or more N-substituted maleimide groups in one molecule (hereinafter referred to as "maleimide compound (B)") is not particularly limited as long as it has two or more N-substituted maleimide groups in one molecule. If the resin composition contains maleimide compound (B), the dielectric loss factor of the cured resin composition can be reduced. Furthermore, since maleimide compound (B) reacts effectively with the aforementioned modified polyphenylene ether compound (A), it is believed that high heat resistance can be obtained. Moreover, it is believed that it also helps to increase the glass transition temperature of the cured resin composition.

[0077] As a preferred example of maleimide compound (B), a maleimide compound (B) having an intramolecular phenyl maleimide group can be cited. By using a maleimide compound having an intramolecular phenyl maleimide group as maleimide compound (B), the glass transition temperature of the cured resin composition can be increased.

[0078] Examples of the aforementioned maleimide compound (B) include: 4,4'-diphenylmethane bismaleimide, polyphenylmethane maleimide, m-phenylene bismaleimide, 2,2-bis[4-(4-maleimidephenoxy)phenyl]propane, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, 4-methyl-1,3-phenylene bismaleimide; biphenyl aralkyl type maleimide resins; and maleimide compounds having a phenylmaleimide group and a meta-substituted arylene group in the molecule.

[0079] Commercially available products can also be used as the maleimide compound (B). Specifically, as 4,4'-diphenylmethane bismaleimide, for example, "BMI-1000" manufactured by Yamato Chemical Industries, Ltd. can be used. Furthermore, as polyphenylmethane maleimide, for example, "BMI-2300" manufactured by Yamato Chemical Industries, Ltd. can be used. As m-phenylene bismaleimide, for example, "BMI-3000" manufactured by Yamato Chemical Industries, Ltd. can be used. As 2,2-bis[4-(4-maleimidephenoxy)phenyl]propane, for example, "BMI-80" manufactured by K.I. Chemical Co., Ltd. can be used. As 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, for example, "BMI-5100" manufactured by Yamato Chemical Industries, Ltd. can be used. As a 4-methyl-1,3-phenylenebismaleimide, "BMI-7000" manufactured by Yamato Chemical Industries, Ltd. can be used, for example. As a biphenyl aryl maleimide resin, "MIR-3000" manufactured by Nippon Kayaku Co., Ltd. can be used, for example. As a maleimide compound having a phenyl maleimide group and a meta-substituted aryl group in the molecule, examples include maleimide compounds represented by the following formula (13), such as "MIR-5000" manufactured by Nippon Kayaku Co., Ltd. It should be noted that in the following formula (13), s represents 1 to 5.

[0080]

[0081] Alternatively, as another preferred example of maleimide compound (B), examples include maleimide compounds (B) having an aliphatic hydrocarbon group within the molecule and not having a phenylmaleimide group within the molecule. The aliphatic hydrocarbon group is not particularly limited, but preferably has 20 or more carbon atoms, more preferably 30 or more. This aliphatic hydrocarbon group can be linear, branched, or alicyclic.

[0082] Examples of maleimide compounds (B) include those shown in formulas (14) to (17) below. Furthermore, commercially available products can be used as these maleimide compounds. Specifically, the maleimide compound shown in formula (14) below can be, for example, BMI-1500 manufactured by Desingner Molecules Inc. The maleimide compound shown in formula (15) below can be, for example, BMI-1700 manufactured by Desingner Molecules Inc. The maleimide compound shown in formula (16) below can be, for example, BMI-689 manufactured by Desingner Molecules Inc. The maleimide compound shown in formula (17) below can be, for example, BMI-3000 manufactured by Desingner Molecules Inc.

[0083]

[0084]

[0085]

[0086]

[0087] These maleimide compounds (B) can be used alone or in combination of two or more.

[0088] The average molecular weight of maleimide compound (B) is preferably 400 to 2000, more preferably 400 to 1500, and even more preferably 500 to 1000. In this specification, the average molecular weight of maleimide compound (B) refers to the value measured using a conventional molecular weight determination method, namely gel permeation chromatography (GPC). It should be noted that when maleimide compound (B) is a polymer such as an oligomer, the "average molecular weight of maleimide compound (B)" is an exponential average molecular weight.

[0089] The functional group equivalent of the maleimide group in maleimide compound (B) is not particularly limited, but is preferably 200 g / eq. to 1000 g / eq., more preferably 200 g / eq. to 600 g / eq., and even more preferably 200 g / eq. to 400 g / eq. It is believed that if the functional group equivalent of the maleimide group in maleimide compound (B) is within the above range, the dielectric loss factor of the cured product can be reduced, and the water absorption rate can be maintained at a lower level.

[0090] The content of maleimide compound (B) is not particularly limited, but is preferably 20% by mass or more, more preferably 35% by mass or more, and even more preferably 40% by mass or more, relative to the total amount of resin component containing maleimide compound (B). Furthermore, the content of maleimide compound (B) relative to the total amount of resin component containing maleimide compound (B) is preferably 90% by mass or less, more preferably 75% by mass or less, and even more preferably 65% ​​by mass or less.

[0091] It should be noted that the mass ratio of maleimide compound (B) to the aforementioned modified polyphenylene ether compound (A) is as described above.

[0092] [Inorganic packing (C)]

[0093] (Titanium acid compound filler (C-1))

[0094] The inorganic filler (C) includes titanate compound filler (C-1). Furthermore, the titanate compound filler (C-1) as the inorganic filler (C) includes one or more fillers selected from the group consisting of strontium titanate, calcium titanate and titanium oxide (including one or more fillers containing substances (materials) selected from the group consisting of strontium titanate, calcium titanate and titanium oxide).

[0095] Including one or more fillers selected from these as inorganic fillers (C) can improve the relative permittivity of the cured product. From the viewpoint of more reliably improving the relative permittivity of the cured product, the titanate compound filler (C-1) preferably includes one or more fillers selected from the group consisting of strontium titanate and calcium titanate (fillers including one or more substances (materials) selected from the group consisting of strontium titanate and calcium titanate). Furthermore, from the viewpoint of particularly improving the relative permittivity of the cured product, the titanate compound filler (C-1) is more preferably a filler including strontium titanate filler (fillers including substances (materials) containing strontium titanate).

[0096] Furthermore, in the resin composition of this embodiment, the total content of one or more fillers selected from the group consisting of strontium titanate, calcium titanate and titanium oxide satisfies the condition that it is 50% by mass or more relative to the total amount of inorganic filler (C), and 100 parts by mass or more and 400 parts by mass or less relative to 100 parts by mass of modified polyphenylene ether compound (A) and maleimide compound (B).

[0097] By ensuring that the total content is 50% or more by mass relative to the total amount of inorganic filler (C), and 100 parts by mass or more relative to 100 parts by mass of modified polyphenylene ether compound (A) and maleimide compound (B), the cured resin composition can be improved to a desired relative permittivity (e.g., a relative permittivity of 5.0 or more at 10 GHz). Furthermore, by ensuring that the total content is 400 parts by mass or less relative to 100 parts by mass of modified polyphenylene ether compound (A) and maleimide compound (B), the dielectric loss factor of the cured resin composition can be maintained at a low value. In addition, it is believed that the formability of the resin composition can also be maintained in a good manner.

[0098] The total content of one or more fillers selected from the three fillers, relative to the total amount of inorganic filler (C), is preferably 60% by mass or more, more preferably 75% by mass or more, even more preferably 85% by mass or more, and particularly preferably a value selected from the group consisting of 87% by mass, 90% by mass, 93% by mass, and 95% by mass or more. There is no particular upper limit to the total content of one or more fillers selected from the three fillers; this content may also be 100% by mass relative to the total amount of inorganic filler (C).

[0099] Furthermore, the total content of one or more fillers selected from the three fillers is preferably 120 parts by mass or more, more preferably 130 parts by mass or more, and even more preferably 135 parts by mass or more, and particularly preferably a value selected from the group consisting of 140 parts by mass, 143 parts by mass, 145 parts by mass, and 148 parts by mass or more, relative to 100 parts by mass of modified polyphenylene ether compound (A) and maleimide compound (B). The total content of one or more fillers selected from the three fillers is preferably 380 parts by mass or less, more preferably 360 parts by mass or less, and even more preferably 340 parts by mass or less, and particularly preferably a value selected from the group consisting of 330 parts by mass, 320 parts by mass, 310 parts by mass, 300 parts by mass, 290 parts by mass, 280 parts by mass, and 270 parts by mass or less, relative to 100 parts by mass of modified polyphenylene ether compound (A) and maleimide compound (B).

[0100] The shape of one or more of the three fillers selected is preferably a particle shape. Specifically, the titanate compound filler (C-1) includes one or more fillers selected from the group consisting of strontium titanate particles, calcium titanate particles, and titanium oxide particles. These particles are not particularly limited, and examples include titanate compound particles obtained by conventional synthesis methods such as precipitation, solid-state methods, and electrofusion methods.

[0101] When one or more of the fillers selected from the three fillers are in particle shape, the average particle size (cumulative 50% diameter (D50) on a volume basis) of the strontium titanate particles, calcium titanate particles, and / or titanium oxide particles is not particularly limited, but is preferably 0.1 μm to 10 μm, more preferably 0.5 μm to 5 μm, and even more preferably 0.5 μm to 3 μm. It is believed that if the average particle size of one or more of the fillers selected from the three fillers is within the above range, the relative permittivity of the cured resin composition can be improved more reliably, and the resin composition can have good formability in the semi-cured state.

[0102] When one or more of the three fillers are selected in particle form, the specific gravity of strontium titanate particles, calcium titanate particles, and / or titanium oxide particles is not particularly limited, but is preferably 3 g / cm³. 3 ~6g / cm 3 More preferably 3g / cm 3 ~5.5g / cm 3 .

[0103] It should be noted that the titanate compound filler (C-1) used as the inorganic filler (C) may also include titanate compound fillers (C-1) other than those containing strontium titanate, calcium titanate, and titanium oxide, provided that the conditions regarding the total content of strontium titanate, calcium titanate, and titanium oxide as described in this embodiment are met and the effects of the high relative permittivity and low dielectric loss factor described in this embodiment are not compromised. Examples of such titanate compound fillers (C-1) include aluminum titanate, magnesium titanate, zinc titanate, lanthanum titanate, neodymium titanate, and barium titanate (more specifically, fillers containing these substances (materials)).

[0104] (Other packing materials (C-2))

[0105] The inorganic filler (C) may also include other fillers (C-2) different from the titanate compound filler (C-1), provided that the total content of strontium titanate, calcium titanate, and titanium oxide described in this embodiment is satisfied and does not impair the effects of the high relative permittivity and low dielectric loss factor described in this embodiment. If the resin composition also contains other fillers (C-2) different from the titanate compound filler (C-1), it is expected to improve the low dielectric loss factor, heat resistance, flame retardancy, and suppression of the coefficient of thermal expansion of the cured resin composition.

[0106] Specifically, other fillers (C-2) include, for example: metal oxides, metal hydroxides, molybdates, nitrides, titanates, anhydrous magnesium carbonate and other magnesium carbonate, calcium carbonate, quartz glass, talc, aluminum borate, barium sulfate and other fillers (more specifically, fillers containing these substances (materials)).

[0107] Specifically, examples of metal oxide fillers include, for example, silica, alumina, magnesium oxide, mica, etc. (more specifically, fillers containing these substances (materials)). Examples of metal hydroxide fillers include, for example, magnesium hydroxide, aluminum hydroxide, etc. (more specifically, fillers containing these substances (materials)). Examples of molybdate fillers include, for example, zinc molybdate, calcium molybdate, magnesium molybdate, etc. (more specifically, fillers containing these substances (materials)). Examples of nitride fillers include, for example, aluminum nitride, boron nitride, etc. (more specifically, fillers containing these substances (materials)). Among these, other fillers (C-2) preferably include silica fillers. Furthermore, these other fillers (C-2) can be used alone or in combination of two or more.

[0108] When the resin composition contains other fillers (C-2), their content can be appropriately adjusted as described above within the range that satisfies the conditions for the total content of strontium titanate, calcium titanate and titanium oxide involved in this embodiment and does not impair the effects of the high relative permittivity and low dielectric loss factor involved in this embodiment.

[0109] The content of other fillers (C-2) (which is the total content when multiple other fillers (C-2) are included) needs to be appropriately set according to the type of filler. For example, the content of these other fillers (C-2) relative to the total amount of inorganic filler (C) is preferably 40% by mass or less, more preferably 25% by mass or less, even more preferably 15% by mass or less, and particularly preferably 5% by mass or less.

[0110] Furthermore, the titanate compound filler (C-1) and any other fillers (C-2) included as inorganic fillers (C) may also be inorganic fillers (C) that have undergone surface treatment. Examples of such surface treatment include treatment with a silane coupling agent described later.

[0111] [Reaction initiator (D)]

[0112] The resin composition may also contain a reaction initiator (D) (catalyst). The reaction initiator (D) is not particularly limited as long as it can promote the curing reaction of the resin composition. Specifically, examples of reaction initiators (D) include azo compounds, peroxides, metal oxides, imidazole compounds, phosphorus-based curing accelerators, and amine-based curing accelerators.

[0113] Examples of azo compounds include 2,2'-azobis(2,4,4-trimethylpentane), 2,2'-azobis(N-butyl-2-methylpropionamide), and 2,2'-azobis(2-methylbutyronitrile).

[0114] Examples of peroxides include: α,α'-di(tert-butylperoxy)diisopropylbenzene, 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne, benzoyl peroxide, 3,3',5,5'-tetramethyl-1,4-diphenol benzoquinone, chloroquinone, 2,4,6-tritert-butylphenoxy, tert-butylperoxyisopropyl monocarbonate, azobisisobutyronitrile, etc.

[0115] Examples of metal oxides include zinc octanoate, tin octanoate, zinc naphthenate, cobalt naphthenate, tin stearate, and zinc stearate.

[0116] The reaction initiator (D) can be used alone or in combination of two or more.

[0117] When the resin composition contains a reaction initiator (D), its content can be appropriately set in a way that does not impair the effects of the high relative permittivity and low dielectric loss factor involved in this embodiment. For example, it can be 0.05 parts by mass or more and 2 parts by mass or less relative to 100 parts by mass of the resin component.

[0118] [Silane coupling agent (E)]

[0119] The resin composition may also contain a silane coupling agent (E). The silane coupling agent (E) may be included in the resin composition as an additive, or it may be included as a silane coupling agent (E) for which the inorganic filler (C) contained in the resin composition has been pre-treated. Furthermore, in the case of prepregs, the prepreg may contain the silane coupling agent (E) as a silane coupling agent (E) for which the fibrous substrate has been pre-treated.

[0120] The silane coupling agent (E) is not particularly limited, but examples include silane coupling agents (E) having at least one functional group selected from the group consisting of vinyl, styrene, methacryloyl, acryloyl, phenylamino, isocyanurate, urea, mercapto, isocyanate, epoxy, and anhydride groups.

[0121] Examples of vinyl-containing silane coupling agents (E) include vinyltriethoxysilane and vinyltrimethoxysilane. Examples of styrene-containing silane coupling agents (E) include p-styrenetrimethoxysilane and p-styrenetriethoxysilane. Examples of methacrylyl-containing silane coupling agents (E) include 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, and 3-methacryloxypropylethyldiethoxysilane. Examples of acrylyl-containing silane coupling agents (E) include 3-acryloxypropyltrimethoxysilane and 3-acryloxypropyltriethoxysilane. Examples of silane coupling agents (E) containing phenylamino groups include N-phenyl-3-aminopropyltrimethoxysilane and N-phenyl-3-aminopropyltriethoxysilane.

[0122] These silane coupling agents (E) can be used alone or in combination of two or more.

[0123] When the resin composition contains a silane coupling agent (E), its content can be appropriately set in a way that does not impair the effects of the high relative permittivity and low dielectric loss factor involved in this embodiment. For example, it can be 0.05 parts by mass or more and 3 parts by mass or less relative to 100 parts by mass of the resin component.

[0124] [Other ingredients]

[0125] The resin composition may contain, as needed, components other than the modified polyphenylene ether compound (A), maleimide compound (B), and inorganic filler (C) containing titanate compound filler (C-1) as described above, and optionally included reaction initiators (D) and silane coupling agents (E), to a extent that does not impair the effects of the high relative permittivity and low dielectric loss factor involved in this embodiment. Examples of other components include, for instance, curing agents, flame retardants, curing accelerators, polymerization retardants, polymerization inhibitors, dispersants, homogenizers, defoamers, antioxidants, heat stabilizers, antistatic agents, ultraviolet absorbers, dyes or pigments, lubricants, and other additives.

[0126] The resin composition may contain, as needed, a curing agent that reacts with at least one of the modified polyphenylene ether compound (A) and maleimide compound (B) to facilitate the curing of the resin composition, to a extent that it does not impair the effects of the high relative permittivity and low dielectric loss factor involved in this embodiment. Examples of curing agents include epoxy compounds, methacrylate compounds, acrylate compounds, cyanate ester compounds, reactive ester compounds, benzoxazine compounds, allyl compounds, etc.

[0127] Examples of epoxy compounds include: bisphenol-type epoxy compounds such as bisphenol A type epoxy compounds, phenolic aldehyde type epoxy compounds, cresol aldehyde type epoxy compounds, dicyclopentadiene type epoxy compounds, bisphenol A aldehyde type epoxy compounds, biphenyl aryl type epoxy compounds, and epoxy compounds containing a naphthalene ring. Furthermore, epoxy resins, which are polymers of these epoxy compounds, are also included.

[0128] Examples of methacrylate compounds include monofunctional and polyfunctional methacrylate compounds. Examples of monofunctional methacrylate compounds include methyl methacrylate, ethyl methacrylate, propyl methacrylate, and butyl methacrylate. Examples of polyfunctional methacrylate compounds include dimethacrylate compounds such as tricyclodecanediethanol dimethacrylate (DCP).

[0129] Examples of acrylate compounds include monofunctional and polyfunctional acrylate compounds. Examples of monofunctional acrylate compounds include methyl acrylate, ethyl acrylate, propyl acrylate, and butyl acrylate. Examples of polyfunctional acrylate compounds include diacrylate compounds such as tricyclodecanediethanol diacrylate.

[0130] Examples of cyanate ester compounds include 2,2-bis(4-cyanooxyphenyl)propane, bis(3,5-dimethyl-4-cyanooxyphenyl)methane, and 2,2-bis(4-cyanooxyphenyl)ethane.

[0131] Examples of active ester compounds include: benzenecarboxylic acid active ester, benzenedicarboxylic acid active ester, benzenetricarboxylic acid active ester, benzenetetracarboxylic acid active ester, naphthalenecarboxylicacid active ester, naphthalenedicarboxylic acid active ester, naphthalenetricarboxylic acid active ester, naphthalenetetracarboxylic acid active ester, fluorenecarboxylic acid active ester, fluorenedicarboxylic acid active ester, fluorenetricarboxylic acid active ester, and fluorenetetracarboxylic acid active ester.

[0132] Examples of benzoxazine compounds include, for example, benzoxazine resins.

[0133] Examples of allyl compounds include: triallyl isocyanurate compounds such as triallyl isocyanurate (TAIC), diallyl bisphenol compounds, diallyl phthalate (DAP), etc.

[0134] These curing agents can be used alone or in combination of two or more.

[0135] The weight-average molecular weight (Mw) of the curing agent is not particularly limited, but is preferably 100 to 5000, more preferably 100 to 4000, and even more preferably 100 to 3000. If the weight-average molecular weight (Mw) of the curing agent is within this range, a resin composition with superior heat resistance of the cured product can be obtained. The weight-average molecular weight (Mw) of the curing agent is a value determined using a conventional molecular weight determination method, namely gel permeation chromatography (GPC).

[0136] The average number of functional groups in each molecule of curing agent that contribute to the reaction during the curing of the resin composition (number of functional groups) varies depending on the weight-average molecular weight of the curing agent. From the viewpoint of the heat resistance of the cured product and the preservation and flowability of the resin composition, it is preferably 1 to 20, and more preferably 2 to 18.

[0137] Resin compositions may also contain flame retardants. The presence of flame retardants improves the flame retardancy of the cured resin composition. The type of flame retardant is not particularly limited. Specifically, in fields using halogenated flame retardants such as bromine-based flame retardants, from the viewpoint of suppressing the decrease in heat resistance, the preferred flame retardants are substances with a melting point of 300°C or higher, such as ethylenedipentabromobenzene, ethylenebistetrabromoimide, decabromodiphenyl ether, tetradecylbromodiphenoxybenzene, and bromostyrene compounds that react with polymerizable compounds. Furthermore, in fields requiring halogen-free properties, phosphorus-containing flame retardants (phosphorus-based flame retardants) are preferred. Phosphorus-based flame retardants are not particularly limited, but examples include: phosphate ester-based flame retardants, phosphazene-based flame retardants, bisdiphenylphosphine-based flame retardants, and phosphinate-based flame retardants. Examples of phosphate ester-based flame retardants include polyphosphate condensates of bis(xyl)phosphine. Examples of phosphazene-based flame retardants include phenoxyphosphazene. Examples of bis(xyl)phosphine-based flame retardants include xylenebis(diphenylphosphine). Examples of phosphinate-based flame retardants include metal salts of dialkyl aluminum hypophosphite. These flame retardants can be used alone or in combination of two or more.

[0138] [Physical Properties of the Resin Composition]

[0139] The cured resin composition of this embodiment has a relative permittivity of 5.0 or higher at a frequency of 10 GHz. By making the cured resin composition have a relative permittivity of 5.0 or higher at a frequency of 10 GHz, it is suitable for forming an insulating layer disposed in a wiring board that can withstand high frequencies.

[0140] The relative permittivity of the cured resin composition at a frequency of 10 GHz is more preferably 5.5 or higher, more preferably 6.0 or higher, and particularly preferably a value selected from the group consisting of 6.4, 6.8, 7.0, 7.3, 7.5, 8.0, and 8.4 or higher. Furthermore, the upper limit of the relative permittivity of the cured resin composition at a frequency of 10 GHz is not particularly limited, for example, it is 15.0 or lower.

[0141] In order to obtain the relative permittivity within the range of this higher value, as described above, it is necessary to adjust the total content of one or more fillers selected from the group consisting of strontium titanate, calcium titanate and titanium oxide to be 50% by mass or more relative to the total amount of inorganic filler (C), and to adjust the total content of the one or more fillers to be 100 parts by mass or more relative to 100 parts by mass of modified polyphenylene ether compound (A) and maleimide compound (B).

[0142] [Uses of the resin composition]

[0143] The resin composition involved in this embodiment is mainly used in the manufacture of prepregs, as described below. In addition, the resin composition is used not only in the manufacture of prepregs, but also in the formation of resin layers disposed on resin-coated metal foils and resin-coated films, and in the formation of insulating layers disposed on metal foil laminates and wiring boards.

[0144] Furthermore, according to the resin composition of this embodiment, a cured product with a high relative permittivity and a low dielectric loss factor can be obtained. Therefore, the resin composition is suitable for forming an insulating layer in wiring boards for antennas, antenna substrates for millimeter-wave radar, and other wiring boards designed for high frequencies. In other words, the resin composition of this embodiment is suitable for manufacturing wiring boards designed for high frequencies.

[0145] There are no particular limitations on high-frequency wiring boards. Examples include wiring boards with small spacing between wires (the distance between adjacent wires), wiring boards with small wire width (the distance of the wires perpendicular to the length direction), and multi-layer wiring boards.

[0146] The wiring board can be a multilayer wiring board with four or more circuit layers. The resin composition according to this embodiment is well used as the insulating material for the insulating layer of this multilayer wiring board. According to the resin composition according to this embodiment, even with such a multilayer wiring board, higher wiring density can be achieved, signal transmission speed can be increased, and signal loss during transmission can be reduced. Furthermore, when applied to multilayer wiring boards with conductive through holes and / or vias, higher signal transmission speed can be achieved, and signal loss during transmission can be reduced.

[0147] [Preparation method of resin composition]

[0148] The preparation method of the resin composition involved in this embodiment is not particularly limited, and it can be prepared by any method known to those skilled in the art. Examples of methods for preparing the resin composition include: mixing a modified polyphenylene ether compound (A) and a maleimide compound (B), along with any other added components, in an appropriate ratio, and then adding an inorganic filler (C) containing a titanate compound filler (C-1). Specifically, when obtaining a varnish-like composition containing an organic solvent, the method described in the following description of the prepreg can be used.

[0149] <Prepreg, metal foil laminate, wiring board, resin-coated metal foil, and resin-coated film>

[0150] Next, we will describe the wiring board prepreg, the metal foil laminate, the wiring board, the resin-coated metal foil, and the resin-coated film using the resin composition described in the foregoing embodiments.

[0151] [Prepreg]

[0152] Figure 1 This is a schematic cross-sectional view illustrating an example of a prepreg according to an embodiment of the present invention. Figure 1 In the text, each symbol represents: 1. Prepreg, 2. Resin composition or semi-cured resin composition, and 3. Fiber substrate.

[0153] like Figure 1 As shown, the prepreg 1 comprises: a resin composition or a semi-cured product of the resin composition 2; and a fibrous substrate 3. Specifically, the prepreg 1 comprises: a resin composition or a semi-cured product of the resin composition 2; and a fibrous substrate 3 present in the resin composition or the semi-cured product of the resin composition 2.

[0154] In this specification, "semi-cured product" refers to a composition that has been cured to a state where it can be further cured. That is, semi-cured product 2 is a resin composition that has been partially cured (benzened). Specifically, when the resin composition is heated, its viscosity initially decreases slowly. Then, the resin composition begins to cure, and its viscosity slowly increases. In this case, semi-cured product 2 refers to the state of the resin composition from the time the viscosity begins to increase until the resin composition is fully cured.

[0155] The prepreg 1 obtained using the resin composition described in the foregoing embodiments may contain a semi-cured product 2 of the resin composition as described above, or it may contain the resin composition itself in an uncured state. That is, the prepreg 1 according to this embodiment may contain a semi-cured product 2 of the resin composition (a B-stage resin composition) and a fibrous substrate 3, or it may contain a resin composition before curing (a A-stage resin composition) and a fibrous substrate 3. It should be noted that the resin composition or the semi-cured product 2 of the resin composition may be a substance obtained by heating and / or drying the resin composition according to the foregoing embodiments.

[0156] The resin compositions described in the foregoing embodiments are mostly prepared in the form of varnish and used as resin varnishes when manufacturing prepreg 1, resin-coated films (described later), resin-coated metal foils, etc. This resin varnish can be prepared, for example, by the method described below.

[0157] First, the resin components, reaction initiator, and other components soluble in organic solvents are added to the organic solvent and dissolved. At this point, the mixture may be heated if necessary. Then, inorganic fillers, which are insoluble in organic solvents, are added to the mixture, and dispersed to a specified dispersion state using a ball mill, bead mill, planetary mixer, roller mill, or similar equipment. As a result, a varnish-like resin composition can be prepared. There are no particular limitations on the organic solvents that can dissolve the modified polyphenylene ether compound (A), the maleimide compound (B), and any curing agent added as needed, without hindering the curing reaction. Examples of organic solvents include toluene, methyl ethyl ketone, cyclohexanone, cyclopentanone, methylcyclohexane, dimethylformamide, and propylene glycol monomethyl ether acetate. These organic solvents may be used alone or in combination.

[0158] As a method for manufacturing prepreg 1 using a varnish-like resin composition, examples include: impregnating a varnish-like resin composition into a fibrous substrate 3 and then drying it.

[0159] The fibrous substrate 3 used in manufacturing the prepreg 1 can be categorized as follows: glass cloth, aramid cloth, polyester cloth, LCP (liquid crystal polymer) nonwoven fabric, glass nonwoven fabric, aramid nonwoven fabric, polyester nonwoven fabric, pulp paper, cotton linter paper, etc. Among these, if glass cloth is used as the fibrous substrate 3, a laminate with excellent mechanical strength can be obtained. In particular, glass cloth that has undergone flattening processing is preferred. Specifically, there is no particular limitation on the type of glass cloth, and examples include low dielectric constant glass cloths such as E glass, S glass, NE glass, Q glass, and L glass. Flattening processing can be performed, for example, by continuously applying appropriate pressure to the glass cloth with pressure rollers to compress the yarn into a flat shape. It should be noted that the thickness of the fibrous substrate 3 is not particularly limited, and a typical thickness of 0.08 mm to 0.3 mm can be used, for example.

[0160] The impregnation of the resin varnish (resin composition) into the fibrous substrate 3 can be carried out by impregnation and / or coating, etc. This impregnation can be repeated multiple times as needed. In this case, multiple resin varnishes with different compositions and / or concentrations can be used for repeated impregnation to ultimately adjust to the desired composition (content ratio) and / or resin amount.

[0161] The fibrous substrate 3, impregnated with a resin varnish (resin composition), is heated under desired heating conditions, for example, at a temperature of 40°C to 180°C, for about 1 minute to 10 minutes. By heating, the solvent evaporates from the varnish, thereby reducing or removing the solvent, and a prepreg 1 in a pre-cured state (for stage A resin composition) or a semi-cured state (for stage B resin composition) can be obtained.

[0162] [Metal Foil Coated Laminate]

[0163] Figure 2 This is a schematic cross-sectional view illustrating an example of a metal foil laminate according to an embodiment of the present invention. Figure 2 In the diagram, each symbol represents: metal foil laminate 11, insulating layer 12, and metal foil 13, respectively.

[0164] like Figure 2 As shown, the metal foil laminate 11 includes: an insulating layer 12 comprising a cured resin composition of the aforementioned embodiments or a cured prepreg 1; and a metal foil 13.

[0165] The metal foil 13 is not particularly limited, and any metal foil known to those skilled in the art that is commonly used for metal foil laminates 11, wiring boards, etc. can be used. For example, copper foil, aluminum foil, etc. can be listed as metal foil 13.

[0166] The thickness of the metal foil 13 can be appropriately set according to the desired purpose. For example, the thickness of the metal foil 13 can be set to about 0.2 μm to 70 μm. For example, when the thickness of the metal foil 13 is less than 10 μm, in order to improve operability, the metal foil 13 can also be a carrier-supported copper foil with a release layer and a carrier.

[0167] The method of manufacturing the metal foil laminate 11 is not particularly limited. For example, it can be manufactured not only using the aforementioned prepreg 1, but also using the resin-coated metal foil and / or resin-coated film described later.

[0168] Specifically, one or more sheets of prepreg 1, resin-coated metal foil (described later), and / or resin-coated film are taken, and copper foil or other metal foil 13 is overlapped on both upper and lower surfaces or one surface. The sheets are then heated and pressurized to form a laminate. As a result, a laminate with metal foil on both sides or one side can be produced. The heating and pressing conditions can be appropriately set according to the thickness of the laminate being manufactured, the type of resin composition, etc. For example, the heating and pressing conditions can be set to 170°C–230°C, 1.5 MPa–5.0 MPa, and 60–150 minutes.

[0169] Furthermore, the metal foil laminate 11 can be manufactured without using the prepreg 1, the resin-containing metal foil described later, and / or the resin-containing film. For example, the aforementioned resin varnish can be applied to the metal foil 13 by coating or the like, and after forming a layer containing the resin composition on the metal foil 13, the metal foil laminate 11 can be manufactured by heating and pressing. It should be noted that the application of coating or the like can be repeated multiple times as needed. In addition, at this time, multiple resin varnishes with different compositions or concentrations can be used to repeatedly apply coating or the like, thereby adjusting the composition (content ratio) and resin amount, so as to finally manufacture the metal foil laminate 11 with the desired composition (content ratio) and resin amount.

[0170] [Wiring board]

[0171] Figure 3 This is a schematic cross-sectional view illustrating an example of a wiring board according to an embodiment of the present invention. Figure 3 In the diagram, each symbol represents: insulation layer 12, wiring 14, and wiring board 21.

[0172] like Figure 3 As shown, the wiring board 21 includes: an insulating layer 12 containing a cured resin composition of the aforementioned embodiments or a cured prepreg 1; and wiring 14 disposed on the insulating layer 12.

[0173] The manufacturing method of the wiring board 21 is not particularly limited. For example, a method can be used to form a circuit by etching the metal foil 13 on the surface of the aforementioned metal foil laminate 11, thereby obtaining a wiring board 21 on the surface of the laminate with conductor patterns (wiring 14) for the circuit. In addition to the methods described above, other methods for forming the circuit include, for example, using a semi-additive process (SAP) or a modified semi-additive process (MSAP).

[0174] [Resin-coated metal foil]

[0175] Figure 4 This is a schematic cross-sectional view illustrating an example of a resin-coated metal foil according to an embodiment of the present invention. Figure 4 In the diagram, each symbol represents: metal foil 13, resin-coated metal foil 31, and resin layer 32.

[0176] like Figure 4 As shown, the resin-coated metal foil 31 according to this embodiment has the following configuration: it is formed by laminating a resin layer 32 containing the resin composition or a semi-cured product 2 of the resin composition described in the aforementioned embodiment and a metal foil 13. That is, the resin-coated metal foil 31 may include: a resin layer 32 containing a resin composition before curing (a first-order resin composition); and a metal foil 13, or it may include: a resin layer 32 containing a semi-cured product 2 of the resin composition (a second-order resin composition); and a metal foil 13. It should be noted that the metal foil 13 is the same as the metal foil 13 of the aforementioned metal foil laminate 11.

[0177] As Figure 4 An example of the method for manufacturing the resin-coated metal foil 31 shown can be illustrated as follows. For example, firstly, the aforementioned resin varnish is applied to the surface of a metal foil 13, such as a copper foil, and then dried by heating to allow the solvent to evaporate from the varnish. Then, the resin-coated metal foil 31 can be manufactured by reducing or removing the solvent.

[0178] Examples of coating methods include bar coaters, comma coaters, die coaters, roller coaters, and gravure coaters. The heating and drying conditions can be set to the desired conditions without particular limitation; for example, heating at 50°C to 180°C for approximately 0.1 to 10 minutes is acceptable. The goal is to obtain a resin-coated metal foil 31 in either a pre-cured state (for the first-stage resin composition) or a semi-cured state (for the second-stage resin composition) after heating and drying. It should be noted that multiple coatings can be repeated as needed. Furthermore, applications such as repeated coating with multiple resin varnishes of different compositions or concentrations can be used to adjust the composition (content ratio) and resin amount, ultimately producing a resin-coated metal foil 31 with the desired composition (content ratio) and resin amount.

[0179] The resin-coated metal foil 31 may be equipped with a cover film as needed. The cover film prevents foreign matter from contaminating the resin composition in its semi-cured state. The cover film is not particularly limited as long as it can be peeled off without damaging the shape of the resin composition. Examples of cover films that can be used include polyolefin films, polyester films, TPX films, films formed by applying a release agent layer to these films, and paper obtained by laminating these films onto a paper substrate.

[0180] [Resin-coated membrane]

[0181] Figure 5 This is a schematic cross-sectional view illustrating an example of a resin-coated film according to an embodiment of the present invention. Figure 5 In the diagram, each symbol represents: the resin-coated membrane 41, the resin layer 42, and the membrane support substrate 43.

[0182] like Figure 5 As shown, the resin-bearing membrane 41 has the following configuration: a resin layer 42 comprising the resin composition or a semi-cured product 2 of the resin composition described in the aforementioned embodiments and a membrane support substrate 43 are laminated together. That is, the resin-bearing membrane 41 may comprise: a resin layer 42 comprising the resin composition before curing (a type A resin composition); and a membrane support substrate 43; or it may comprise: a resin layer 42 comprising the semi-cured product 2 of the resin composition (a type B resin composition); and a membrane support substrate 43. Furthermore, the resin layer 42 may or may not comprise the fibrous substrate 3, as long as it comprises the resin composition or the semi-cured product 2 of the resin composition described in the aforementioned embodiments.

[0183] As Figure 5An example of the method for manufacturing the resin-coated membrane 41 shown can be illustrated as follows. For example, firstly, the aforementioned resin varnish is applied to the surface of the membrane support substrate 43 and then heated and dried. Then, the solvent is evaporated from the varnish to reduce or remove the solvent, thereby enabling the manufacture of the resin-coated membrane 41.

[0184] The coating method and heating and drying conditions are the same as those for the aforementioned manufacturing method of the resin-coated metal foil 31, and are set to obtain the resin-coated metal foil 31 in the pre-cured state (stage A resin composition) or the semi-cured state (stage B resin composition).

[0185] The membrane support substrate 43 is not particularly limited as long as it is any substrate known to those skilled in the art. For example, examples of membrane support substrates 43 include polyimide film, PET (polyethylene terephthalate) film, polyester film, polyurethane film, polyetheretherketone film, polyphenylene sulfide film, aramid film, polycarbonate film, polyarylate film, and other electrically insulating films.

[0186] The resin-coated film 41 also has a covering film, etc., just like the resin-coated metal foil 31 mentioned above.

[0187] As described above, the prepreg, resin-coated metal foil, resin-coated film, and metal foil laminate involved in this embodiment are manufactured using the resin compositions described in the aforementioned embodiments, which have a high relative permittivity and low dielectric loss factor of the cured material. Therefore, as described above, these are suitable for forming insulating layers disposed in wiring boards that cope with high frequencies.

[0188] This specification discloses various implementation techniques as described above, and its main technical features are summarized below.

[0189] The first technical solution of the present invention relates to a resin composition comprising: a polyphenylene ether compound (A) having carbon-carbon unsaturated double bonds; a maleimide compound (B) having two or more N-substituted maleimide groups in one molecule; and an inorganic filler (C) comprising a titanate compound filler (C-1), wherein the titanate compound filler (C-1) comprises one or more fillers selected from the group consisting of strontium titanate, calcium titanate, and titanium oxide, the total content of the one or more fillers selected from the group consisting of strontium titanate, calcium titanate, and titanium oxide is 50% by mass or more relative to the total amount of the inorganic filler (C), and is 100 parts by mass or more and 400 parts by mass or less relative to 100 parts by mass of the polyphenylene ether compound (A) and the maleimide compound (B).

[0190] The resin composition involved in the second technical solution of the present invention is the resin composition involved in the first technical solution, wherein the polyphenylene ether compound (A) comprises a modified polyphenylene ether compound having at least one of a weight-average molecular weight and a number-average molecular weight of 1000 to 5000.

[0191] The resin composition involved in the third technical solution of the present invention is the resin composition involved in the first or second technical solution, wherein the polyphenylene ether compound (A) comprises a polyphenylene ether compound having at least one group selected from the groups shown in formula (1) and the groups shown in formula (2) above.

[0192] The resin composition involved in the fourth technical solution of the present invention is the resin composition involved in any one of the first to third technical solutions, wherein the functional group equivalent of the maleimide compound (B) is 200 g / eq. to 1000 g / eq.

[0193] The resin composition involved in the fifth technical solution of the present invention is the resin composition involved in any one of the technical solutions from the first to the fourth, wherein the mass ratio of the polyphenylene ether compound (A) to the maleimide compound (B) (the polyphenylene ether compound (A): the maleimide compound (B)) is 20:80 to 80:20.

[0194] The resin composition involved in the sixth technical solution of the present invention is the resin composition involved in any one of the technical solutions 1 to 5, and the inorganic filler (C) further includes other fillers (C-2) different from the titanate compound filler (C-1).

[0195] The resin composition involved in the seventh technical solution of the present invention is the resin composition involved in any one of the first to sixth technical solutions, wherein the cured resin composition has a relative permittivity of 5.0 or higher at a frequency of 10 GHz.

[0196] The eighth technical solution of the present invention relates to a prepreg comprising: a resin composition or a semi-cured product of the resin composition according to any one of the first to seventh technical solutions; and a fibrous substrate.

[0197] The ninth technical solution of the present invention relates to a resin-bearing membrane, comprising: a resin layer containing the resin composition or a semi-cured product of the resin composition according to any one of the first to seventh technical solutions; and a support membrane.

[0198] The tenth technical solution of the present invention relates to a resin-coated metal foil, comprising: a resin layer containing the resin composition or a semi-cured product of the resin composition according to any one of the first to seventh technical solutions; and a metal foil.

[0199] The 11th technical solution of the present invention relates to a metal foil laminate, comprising: an insulating layer comprising a cured resin composition of any one of the technical solutions 1 to 7; and a metal foil.

[0200] The 12th technical solution of the present invention relates to a metal foil laminate, comprising: an insulating layer comprising a cured prepreg of the 8th technical solution; and a metal foil.

[0201] The 13th technical solution of the present invention relates to a wiring board, comprising: an insulating layer comprising a cured resin composition of any one of the technical solutions 1 to 7; and wiring.

[0202] The 14th technical solution of the present invention relates to a wiring board, which includes: an insulating layer comprising a cured prepreg of the 8th technical solution; and wiring.

[0203] Example

[0204] The present invention will be further described in detail below through embodiments; however, the present invention is not limited to any of the embodiments.

[0205] First, the raw materials used to prepare the resin composition of this embodiment are summarized below.

[0206] [Modified polyphenylene ether compound (A)]

[0207] • Modified PPE compound 1: Polyphenylene ether compound with a vinyl benzyl group (ethylene benzyl) at the end ("OPE-2st 1200", Mn1200, Mw1600 manufactured by Mitsubishi Gas Chemical Co., Ltd., represented by the above formula (10) and Ar in formula (10) is phenylene and R1 to R3 are hydrogen atoms and p is 1)

[0208] • Modified PPE compound 2: Polyphenylene ether compounds with vinyl benzyl (ethylene benzyl) at the end (modified polyphenylene ether compounds obtained by reacting polyphenylene ether with chloromethylstyrene).

[0209] Specifically, the modified PPE compound 2 was obtained by the following synthesis method. First, 200 g of polyphenylene ether (SA90 manufactured by SABIC Innovative Plastics Co., Ltd., with two terminal hydroxyl groups and a weight-average molecular weight of Mw 1700), 30 g of a mixture of p-chloromethylstyrene and m-chloromethylstyrene in a mass ratio of 50:50 (chloromethylstyrene:CMS manufactured by Tokyo Chemical Industry Co., Ltd.), 1.227 g of tetrabutylammonium bromide as a phase transfer catalyst, and 400 g of toluene were added to a 1-liter three-necked flask equipped with a temperature regulator, stirring device, cooling equipment, and dropping funnel, and the mixture was stirred. Then, the mixture was stirred until the polyphenylene ether, chloromethylstyrene, and tetrabutylammonium bromide dissolved in toluene. At this point, the mixture was gradually heated until the liquid temperature reached 75°C. Then, an aqueous solution of sodium hydroxide (20 g sodium hydroxide / 20 g water), which is an alkali metal hydroxide, was added dropwise to the solution over 20 minutes. Then, the mixture was stirred at 75°C for 4 hours. Next, the contents of the flask were neutralized with 10% hydrochloric acid by mass, and then a large amount of methanol was added. This caused a precipitate to form in the liquid inside the flask. In other words, the product contained in the reaction solution inside the flask was reprecipitated. Then, the precipitate was removed by filtration, washed three times with a methanol-water mixture at a mass ratio of 80:20, and dried at 80°C for 3 hours under reduced pressure.

[0210] use 1 The obtained solid was analyzed by 1H-NMR (400MHz, CDCl3, TMS). NMR measurements confirmed a peak originating from vinyl benzyl (ethylene benzyl) at 5–7 ppm. This confirmed that the obtained solid was a modified polyphenylene ether compound with vinyl benzyl (ethylene benzyl) as a substituent at the molecule's terminal. Specifically, the obtained solid was confirmed to be a vinyl benzylated polyphenylene ether. The obtained modified polyphenylene ether compound is represented by the above formula (11), where Y in formula (11) is dimethylmethylene (represented by the above formula (9), where R in formula (9) is...). 33 and R 34 A modified polyphenylene ether compound having a methyl group, Ar being a phenylene group, R1 to R3 being hydrogen atoms, and p being 1.

[0211] In addition, the number of terminal functional groups of the modified polyphenylene ether was determined in the following manner.

[0212] First, the modified polyphenylene ether was accurately weighed. This weight is set as X (mg). Then, the weighed modified polyphenylene ether was dissolved in 25 mL of dichloromethane. 100 μL of a 10% by mass solution of tetraethylammonium hydroxide (TEAH) in ethanol (TEAH:ethanol (volume ratio) = 15:85) was added to this solution, and the absorbance (Abs) at 318 nm was measured using a UV spectrophotometer (Shimadzu Corporation UV-1600). Based on this measurement, the number of terminal hydroxyl groups of the modified polyphenylene ether was calculated using the following formula.

[0213] Residual OH content (μmol / g) = [(25×Abs) / (ε×OPL×X)]×106

[0214] Here, ε represents the absorptivity, which is 4700 L / mol·cm. Furthermore, OPL is the unit optical path length, which is 1 cm.

[0215] Furthermore, the calculated residual OH content (number of terminal hydroxyl groups) of the modified polyphenylene ether is almost zero, indicating that almost all the hydroxyl groups in the unmodified polyphenylene ether have been modified. Therefore, the reduction in the number of terminal hydroxyl groups compared to the unmodified polyphenylene ether is equal to the number of terminal hydroxyl groups in the unmodified polyphenylene ether. In other words, the number of terminal functional groups is 2.

[0216] In addition, the intrinsic viscosity (IV) of the modified polyphenylene ether in dichloromethane at 25°C was determined. Specifically, the intrinsic viscosity (IV) of the modified polyphenylene ether in a 0.18 g / 45 ml solution of dichloromethane (at 25°C) was determined using a viscometer (ALS500 Visco System, Schott AG). The result was an intrinsic viscosity (IV) of 0.086 dl / g.

[0217] Furthermore, the molecular weight distribution of the modified polyphenylene ether was determined using GPC. The weight-average molecular weight (Mw) was then calculated based on this molecular weight distribution. The result was that Mw was 1900.

[0218] • Modified PPE compound 3: A modified polyphenylene ether compound in which the terminal hydroxyl groups of polyphenylene ether are modified with methacryl groups (SA9000 manufactured by SABIC Innovative Plastics, with a weight-average molecular weight of Mw2000 and 2 terminal functional groups).

[0219] [Maleimide compound (B)]

[0220] • Maleimide compound 1: The maleimide compound shown in the following formula (18) ("BMI-80" manufactured by K.I Chemical Co., Ltd., with a functional group equivalent of 285 g / eq. of maleimide group and a molecular weight of 570.6)

[0221]

[0222] • Maleimide compound 2: The maleimide compound shown in formula (16) above ("BMI-689" manufactured by the designer's molecular company, with a functional group equivalent of 344.5 g / eq. of maleimide group and a molecular weight of 689)

[0223] • Maleimide compound 3: The maleimide compound shown in formula (13) above (MIR-5000 manufactured by Nippon Kayaku Co., Ltd., with a functional group equivalent of 260 g / eq of maleimide group).

[0224] • Maleimide compound 4: Polyphenylene maleimide (BMI-2300 manufactured by Daiwa Chemical Industry Co., Ltd., with a maleimide functional group equivalent of 180 g / eq. and a molecular weight of 400)

[0225] [Inorganic packing (C)]

[0226] (Titanium acid compound filler (C-1))

[0227] • Strontium titanate particles: "ST-H100" manufactured by Kyoritsu Materials Co., Ltd. (specific gravity 5.1 g / cm³) 3 (Average particle size (D50) 1.32 μm)

[0228] • Calcium titanate particles: "CT" (specific gravity 4g / cm³) manufactured by Fuji Titanium Industry Co., Ltd. 3 Average particle size (D50) 1.9 μm

[0229] • Barium titanate particles: Barium titanate "BT-HP500" manufactured by Kyoritsu Materials Co., Ltd. (specific gravity 6.08 g / cm³) 3 (Average particle size (D50) 1.00 μm)

[0230] (Other packing materials (C-2))

[0231] • Silica filler: "SC2300-SVJ" (specific gravity 2.3 g / cm³) manufactured by Admatechs Company Limited. 3 Average particle size (D50) 0.5 μm

[0232] [Reaction initiator (D)]

[0233] • Peroxide: α,α'-Di(tert-butylperoxide m-isopropyl)benzene (PERBUTYL P (PBP) manufactured by Nippon Oil Co., Ltd.)

[0234] [Silane coupling agent (E)]

[0235] ·3-Methacryloxypropyltrimethoxysilane (a silane coupling agent containing a methacryl group within the molecule, manufactured by Shin-Etsu Chemical Co., Ltd. as "KBM-503")

[0236] Next, the preparation methods of the resin compositions (varnishes) in each embodiment and comparative example, as well as the manufacturing methods of the evaluation substrate (metal foil laminate) 1 and the evaluation substrate (metal foil laminate) 2, are described below.

[0237] <Examples 1-8 and Comparative Examples 1-4>

[0238] (Preparation method of resin composition (varnish))

[0239] In each embodiment and comparative example, all components except the inorganic filler, reaction initiator, and silane coupling agent were added to methyl ethyl ketone in the manner shown in Tables 1 to 3 below (parts by mass) to achieve a solids concentration of 40% by mass, and then mixed. The resulting mixture was then heated at 65°C while being stirred for 60 minutes. Next, the mixture was cooled to 25°C with stirring, and then the inorganic filler, reaction initiator, and silane coupling agent were added according to the formulations shown in Tables 1 to 3 below (parts by mass). The inorganic filler was then dispersed into the mixture using a bead mill. After dispersion, a varnish-like resin composition was obtained.

[0240] (Evaluation of the fabrication method of substrate (metal foil laminate) 1)

[0241] The varnish obtained by the aforementioned method was impregnated into a fibrous substrate (glass cloth: #1067 type, NE glass manufactured by Nitto Boshoku Co., Ltd.), and then heated and dried at 120°C to 150°C for 3 minutes to produce prepreg 1. At this time, the thickness of a single piece of prepreg after curing was adjusted to reach 0.070 mm.

[0242] Twelve sheets of the obtained prepreg were overlapped, and copper foil (GTHMP12 manufactured by Furukawa Electric Industries, Ltd., 12 μm thick) was placed on both sides. This was used as a pressing substrate and heated to 210°C at a heating rate of 3°C / min, and then subjected to heat and pressure at 210°C for 120 minutes and a pressure of 4 MPa. Finally, an evaluation substrate (metal foil laminate) 1 with a thickness of approximately 0.84 mm and copper foil bonded to both surfaces was obtained.

[0243] (Evaluation of the fabrication method of substrate (metal foil laminate) 2)

[0244] The varnish obtained by the aforementioned method was impregnated into a fibrous substrate (glass cloth: #1067 type, NE glass manufactured by Nitto Boshoku Co., Ltd.), and then heated and dried at 120°C to 150°C for 3 minutes to produce prepreg 2. At this time, the thickness of a single piece of prepreg after curing was adjusted to reach 0.100 mm.

[0245] Copper foil (3EC-VLP manufactured by Mitsui Metals Mining Co., Ltd., 12 μm thick) was placed on both sides of the obtained prepreg. It was used as a pressing material and heated to 210°C at a heating rate of 3°C / min, and then subjected to heating and pressurization at 210°C for 120 minutes and a pressure of 4 MPa. Finally, an evaluation substrate (metal foil laminate)2 with a thickness of approximately 0.100 mm and copper foil bonded to both surfaces was obtained.

[0246] First, the following tests were conducted using the prepreg 1 and evaluation substrate 1 of each embodiment and comparative example obtained by the aforementioned method.

[0247] <Evaluation Experiment 1>

[0248] [Dielectric properties (relative permittivity and dielectric loss factor)]

[0249] The bare board (cured prepreg) after removing the copper foil from the evaluation substrate (copper-clad laminate) 1 with a thickness of approximately 0.84 mm obtained by the aforementioned method was cut into pieces 2 mm wide and 100 mm long, and used as test pieces for evaluation. After drying the test pieces in a constant temperature oven maintained at 105°C for 2 hours, they were cooled in a desiccator, and the relative permittivity Dk and dielectric loss factor Df of the test pieces at 10 GHz were measured using the resonant cavity perturbation method. Specifically, the relative permittivity Dk and dielectric loss factor Df of the test pieces at 10 GHz at 25°C were measured using a network analyzer (Keysight Technologies N5230A). With a relative permittivity Dk of 5.0 or higher, the test piece had a high relative permittivity Dk and was evaluated as "qualified". Furthermore, when the dielectric loss factor Df is below 0.005, the dielectric loss factor Df of this test piece is relatively low, and it is evaluated as "qualified".

[0250] [Formability]

[0251] On the copper foil layers on both sides of a copper-clad laminate (manufactured by Panasonic Corporation, model "R-5775", 0.2 mm thick, 35 μm copper foil), a grid-like pattern of conductor wiring was formed to achieve a residual copper content of 20% or 50%. Furthermore, a piece of prepreg 1 obtained by the aforementioned method was laminated on each side of the conductor wiring on this substrate, and a 12 μm thick copper foil (manufactured by Mitsui Metals & Minerals Co., Ltd., "3EC-VLP") was placed on top as the press body. The laminate was heated and pressurized for 120 minutes at a temperature of 210°C and a pressure of 4 MPa to obtain a laminate. Then, the outer copper foil was fully etched to obtain a sample of the laminate. In this sample of the laminate (evaluation laminate), the resin composition derived from prepreg 1 was sufficiently infiltrated between the grid-like pattern circuits with residual copper contents of 20% and 50%, and no voids were formed; therefore, the formability was evaluated as "acceptable". In cases where the resin composition derived from prepreg 1 is sufficiently infiltrated between grid-patterned circuits with a residual copper ratio of 50%, but not sufficiently infiltrated between grid-patterned circuits with a residual copper ratio of 20%, resulting in voids, the formability is evaluated as "good". In cases where the resin composition derived from prepreg 1 is not sufficiently infiltrated between either grid-patterned circuits with residual copper ratios of 20% or 50%, resulting in voids, the evaluation is "unacceptable". It should be noted that voids can be confirmed visually.

[0252] The results of evaluation test 1 in each embodiment and comparative example, along with the formulation composition, are summarized in Tables 1 to 3 below. The formulation amount is expressed as parts by mass relative to 100 parts by mass of resin component. It should be noted that the "-" column in Tables 1 to 3 below indicates that the resin composition of that embodiment or comparative example was not formulated.

[0253]

[0254]

[0255]

[0256] <Inspection>

[0257] As shown in Tables 1 and 2 above, the resin compositions of Examples 1 to 12 comprise a polyphenylene ether compound (A), a maleimide compound (B), and strontium titanate particles or calcium titanate particles as inorganic fillers (C). Furthermore, in the resin compositions of Examples 1 to 12, the content of strontium titanate particles or calcium titanate particles is 50% by mass or more relative to the total amount of inorganic filler (C), and is 100 parts by mass or more and 400 parts by mass or less relative to 100 parts by mass of resin components. The relative permittivity Dk and dielectric loss factor Df of the cured resin compositions were also evaluated as "acceptable". Furthermore, the formability was evaluated as "acceptable" or "good".

[0258] On the other hand, in the resin composition of Comparative Example 1, since the content of strontium titanate particles as inorganic filler (C) is less than 100 parts by mass relative to 100 parts by mass of resin components, the relative permittivity Dk is considered to be reduced.

[0259] In the resin compositions of Comparative Examples 2 and 3, since neither contained strontium titanate particles or calcium titanate particles as inorganic filler (C), the relative permittivity Dk was considered to be reduced. Regarding Comparative Example 3, since the amount of silica filler was excessive relative to 100 parts by mass of the resin composition, it was believed to have also affected the formability.

[0260] In the resin composition of Comparative Example 4, since the content of strontium titanate particles as inorganic filler (C) is less than 50% by mass relative to the total amount of inorganic filler (C), the relative permittivity Dk is considered to be reduced.

[0261] In the resin compositions of Comparative Examples 5 and 6, although the inorganic filler (C) contains titanate compound filler (C), it contains only barium titanate particles other than strontium particles, calcium titanate particles and titanium oxide particles. Therefore, the dielectric loss factor Df is considered to be higher.

[0262] In addition, the following tests were conducted using the evaluation substrates 2 of Examples 1 to 12.

[0263] <Evaluation Experiment 2>

[0264] Glass transition temperature

[0265] The bare board (cured prepreg) after removing the copper foil from the evaluation substrate (copper-clad laminate) 2 with a thickness of approximately 0.100 mm obtained by the aforementioned method was used as the evaluation test piece. The glass transition temperature of the test piece (cured resin composition) was determined using a viscoelastic spectrometer "DMS6100" manufactured by Seiko Instruments Inc. Dynamic viscoelasticity (DMA) was performed in the stretching module at a frequency of 10 Hz. The glass transition temperature (°C) was defined as the temperature at which tanδ reaches its maximum when heated from room temperature to 340°C at a heating rate of 5°C / min. Since the measured glass transition temperature was 200°C or higher, the glass transition temperature of the test piece was deemed sufficiently high.

[0266] Coefficient of thermal expansion

[0267] The bare board, obtained by etching from the evaluation substrate (copper-clad laminate) 2 with a thickness of approximately 0.100 mm obtained by the aforementioned method, after removing the copper foil, was used as a test piece. The coefficient of thermal expansion (CTE) in the substrate surface direction (stretching direction or warp direction of the glass cloth) within a temperature range below the glass transition temperature of the cured resin was measured using the Thermo-mechanical analysis (TMA) method. The measurement was performed in stretching mode using a TMA apparatus (manufactured by Seiko Electronics Nanotechnology Co., Ltd., "TMA6000"). To eliminate the influence of thermal strain during press forming of the test piece, two heating-cooling cycles were repeated, and the average CTE from 50°C to 100°C was measured in the second temperature shift diagram. It should be noted that a smaller measured value indicates a lower CTE, which is preferable. A CTE of 15 or less obtained by measurement is considered sufficiently low. The unit is "ppm / °C". The measurement conditions are described below.

[0268] Measurement conditions;

[0269] • Temperature rise range for the first cycle: 30℃ to glass transition temperature + 20℃

[0270] • Temperature rise range for the second cycle: 30℃~300℃

[0271] • Heating rate: 10℃ / minute, Load: 1g

[0272] • Test piece: 3.5mm (width), 20mm (tensile direction)

[0273] The results of evaluation test 2 for each embodiment, along with the formulation composition, are summarized in Tables 4 and 5 below. The formulation amount is expressed as parts by mass relative to 100 parts by mass of resin component. It should be noted that "-" in the columns of Tables 4 and 5 below indicates that the resin composition of that embodiment was not formulated.

[0274]

[0275]

[0276] <Inspection>

[0277] As shown in Tables 4 and 5 above, it can be seen that the evaluation substrate 1 or evaluation substrate 2 using the resin compositions of Examples 1 to 12 both have sufficiently high glass transition temperatures and sufficiently low coefficients of thermal expansion.

[0278] This application is based on Japanese Patent Application No. 2024-054557, filed on March 28, 2024, the contents of which are incorporated herein by reference.

[0279] The embodiments and examples disclosed herein are illustrative at all points and should not be construed as limiting. The scope of the invention is not defined by the foregoing description, but by the claims, and includes all modifications equivalent to and within the scope of the claims.

[0280] Industrial availability

[0281] According to the present invention, a resin composition capable of producing a cured material with a high relative permittivity and a low dielectric loss factor can be provided. Therefore, this resin composition is suitable for forming insulating layers and the like in wiring boards for antennas, antenna substrates for millimeter-wave radar, and other wiring boards designed for high frequencies.

Claims

1. A resin composition, characterized by contain: Polyphenylene ether compound (A) has carbon-carbon unsaturated double bonds; Maleimide compound (B), having two or more N-substituted maleimide groups in one molecule; and Inorganic filler (C), including titanate compound filler (C-1), wherein, The titanate compound filler (C-1) comprises one or more fillers selected from the group consisting of strontium titanate, calcium titanate, and titanium oxide. The total content of one or more fillers selected from the group consisting of strontium titanate, calcium titanate and titanium oxide is 50% or more by mass relative to the total amount of the inorganic filler (C), and is 100 parts by mass or more and 400 parts by mass relative to 100 parts by mass of the polyphenylene ether compound (A) and the maleimide compound (B).

2. The resin composition according to claim 1, characterized in that, The polyphenylene ether compound (A) comprises a modified polyphenylene ether compound having at least one of a weight-average molecular weight and a number-average molecular weight of 1000 to 5000.

3. The resin composition according to claim 1, characterized in that, The polyphenylene ether compound (A) comprises a polyphenylene ether compound having at least one group selected from the groups shown in formula (1) and formula (2) below. In formula (1), p represents an integer from 0 to 10, Ar represents an aryl group, and R1 to R3 each independently represent a hydrogen atom or an alkyl group. In formula (2), R4 represents a hydrogen atom or an alkyl group.

4. The resin composition according to claim 1, characterized in that, The functional group equivalent of the maleimide compound (B) is 200 g / eq. to 1000 g / eq.

5. The resin composition according to claim 1, characterized in that, The mass ratio of the polyphenylene ether compound (A) to the maleimide compound (B) (the polyphenylene ether compound (A): the maleimide compound (B)) is 20:80 to 80:

20.

6. The resin composition according to claim 1, characterized in that, The inorganic filler (C) also includes other fillers (C-2) that are different from the titanate compound filler (C-1).

7. The resin composition according to claim 1, characterized in that, The cured resin composition has a relative permittivity of 5.0 or higher at a frequency of 10 GHz.

8. A prepreg, characterized by include: The resin composition or the semi-cured product of the resin composition according to any one of claims 1 to 7; as well as Fiber-based substrate.

9. A film with resin, characterized by include: A resin layer comprising the resin composition of any one of claims 1 to 7 or a semi-cured product of the resin composition; as well as Support membrane.

10. A metal foil with resin characterized by include: A resin layer comprising the resin composition of any one of claims 1 to 7 or a semi-cured product of the resin composition; as well as Metal foil.

11. A metal-clad laminate characterized by include: An insulating layer comprising a cured product of the resin composition according to any one of claims 1 to 7; as well as Metal foil.

12. A metal-clad laminate characterized by include: An insulating layer comprising the cured prepreg of claim 8; as well as Metal foil.

13. A wiring board, characterized by include: An insulating layer comprising a cured product of the resin composition according to any one of claims 1 to 7; as well as wiring.

14. A wiring board, characterized by include: An insulating layer comprising the cured prepreg of claim 8; as well as wiring.

Citation Information

Patent Citations

  • Air sterilization device

    JP2024054557A

  • Resin composition, prepreg, resin sheet, laminate board, metal foil-clad laminate board, and printed wiring board

    WO2022172752A1